A homeopathic remedy from arnica, marigold, St. John's wort and comfrey accelerates in vitro wound scratch closure of NIH 3T3 fibroblasts - Hostanska Katarina; Rostock Matthias; Melzer Joerg; Baumgartner Stephan; Saller Reinhard (BMC, 2012)
Abstract Background Drugs of plant origin such as Arnica montana, Calendula officinalis or Hypericum perforatum have been frequently used to promote wound healing. While their effect on wound healing using preparations at pharmacological concentrations was supported by several in vitro and clinical studies, investigations of herbal homeopathic remedies on wound healing process are rare. The objective of this study was to investigate the effect of a commercial low potency homeopathic remedy Similasan® Arnica plus Spray on wound closure in a controlled, blind trial in vitro. Methods We investigated the effect of an ethanolic preparation composed of equal parts of Arnica montana 4x, Calendula officinalis 4x, Hypericum perforatum 4x and Symphytum officinale 6x (0712-2), its succussed hydroalcoholic solvent (0712-1) and unsuccussed solvent (0712-3) on NIH 3T3 fibroblasts. Cell viability was determined by WST-1 assay, cell growth using BrdU uptake, cell migration by chemotaxis assay and wound closure by CytoSelect ™Wound Healing Assay Kit which generated a defined "wound field". All assays were performed in three independent controlled experiments. Results None of the three substances affected cell viability and none showed a stimulating effect on cell proliferation. Preparation (0712-2) exerted a stimulating effect on fibroblast migration (31.9%) vs 14.7% with succussed solvent (0712-1) at 1:100 dilutions (p < 0.001). Unsuccussed solvent (0712-3) had no influence on cell migration (6.3%; p > 0.05). Preparation (0712-2) at a dilution of 1:100 promoted in vitro wound closure by 59.5% and differed significantly (p < 0.001) from succussed solvent (0712-1), which caused 22.1% wound closure. Conclusion Results of this study showed that the low potency homeopathic remedy (0712-2) exerted in vitro wound closure potential in NIH 3T3 fibroblasts. This effect resulted from stimulation of fibroblasts motility rather than of their mitosis.